MODAL SOSIAL PEDAGANG KAKI LIMA (PKL): Studi Kasus pada Event Toboali City On Fire di Kepulauan Bangka Belitung - Syarifah Risma Permatasari; Michael Jeffri Sinabutar (Saskara : Indonesian Journal of Society Studies, 2022)
This research was conducted on 25 July-28 July 2019. The research location was in Toboali, South Bangka, Bangka Belitung Islands at an event held, namely Toboali City On Fire. This study aims to see: 1). Norms as social capital as business development among street vendors, 2). Forms of Trust among street vendors, 3). Benefits of social capital among street vendors to increase the economy. This study uses descriptive qualitative, so in this study the researchers investigated and directly with street vendors and in data collection the researchers also used the accidental sampling method, which the determination of the sample based on chance, that is, anyone who happens to meet the researcher can be used as a sample, if it is considered to be met is suitable as a source of data Based on research, using Coleman's theory, this concept seeks to explain that social capital is the ability of society to achieve common goals within various groups and organizations. (Fukuyama, 1995). With this we know that there is social capital that occurs in the ties of street vendors based on social norms and beliefs, such as they make mutually agreed upon rules so that their business runs smoothly.